Peningkatan Performa Teknis dan Ekonomi Peternakan Ayam Lokal IPB D1 yang Diberikan Tepung Larva Black Soldier Fly : Improved Technical and Economic Performance of IPB D1 Local Chicken Fed with Black Soldier Fly Larva Meal (Jurnal Agroekoteknologi dan Agribisnis, 2022)
Food loss and waste (FLW) and dependence on imported feed ingredients need to be resolved comprehensively. Bioconversion using the Black Soldier Fly (BSF) maggot is applicable to overcome this problem. This study aims to examine the technical and economic performance of IPB D1 local chickens fed BSF maggot in their rations. This study used a completely randomized design (CRD) to observe differences in the production and economic performance of 515 birds (IPB D1). Three treatments (P0, P1, and P2) were observed for ten weeks. BSF maggot meal cost production, production performance, and economic performance were observed in this study. The data were analyzed using descriptive and statistical analysis. The main findings of this research indicated the potential of maggot meal as an alternative source of protein in local chicken rations. Feed efficiency and production performance of IPB D1 chickens given P1 and P2 rations could compete with rations using other protein sources. The economic performance also shows the same thing. However, there are high–economic costs for producing maggot meal. Furthermore, the benefits value by rations P1 and P2 were relatively small compared to control rations. Based on technical and economic performance, maggot meal needs to be developed as a local chicken ration ingredient. However, innovation is necessary to reduce production costs and increase profitability.